PENETAPAN PERWALIAN BAGI ANAK KORBAN TSUNAMI OLEH MAHKAMAH SYARâIAH KOTA BANDA ACEH - Idami, Zahratul (Jurnal Media Hukum, 2010)
Banda Aceh City is in the special condition caused by the tsunami in which some children do not only lose their parents but also siblings, become victims, lose their residence because they were also destroyed by the tsunami, so that they have to live in refugee camps. For these children, guardians are needed to take care of and be responsible for the continuity of the childrenâs lives in fulfilling their needs. Based on that situation, the problems which arise are, then: How does the implementation of the Custody Establishment for children victims of tsunami by the Sharia Court of Banda Aceh City? What are the obstacles faced in implementing the custody establishment referred to and what are the legal consequences? And what are the efforts made to overcome these obstacles? The data collection in this research is obtained through literature study and field research. The data obtained are analyzed using a qualitative approach and descriptive analysis method. The Custody Establishment is doen through Sharia Court decision based on the petitions which meet the specified requirements. In the implementation of post-tsunami custody establishment, the establishment was decided by a single judge because of the circumstances at the time, but after the situation is better, the judge is, then, the panel of judges. The legal consequences of the establishment are the responsibilities of the guardians to the children and the properties of the children under their custody. The efforts made are settling the custody petition that the court has got using existing facilities, and holding seminars or dialogues that discuss the need for rules regarding the supervision of children and the properties of the children who are under custody.Key words: Sharia Court of Banda Aceh, Victims of Tsunami, Custody Establishment